PENGARUH AKTUALISASI DIRI TERHADAP MOTIVASI BERPRESTASI KARYAWAN PT.WIRA KARYA SAKTI JAMBI - Tarmizi, Ahmad (IQTISHODUNA, 2009)
Many theories explain the achievement motivation is influenced by self actualization factor. This research investigates the influence of self actualization to achievement motivation. Data was collected using questionnaires and utilizing purposive non random sampling technique with 56 respondents. Anava Rambang Lugas is used to test the hypothesis. The result shows FoA (6,560) F-tabel 5% (4.03) which means there is significant influence of self actualization to achievement motivation at PT WKS employee.